Parapoxvirus orf virus infection induces an increase in interleukin-8, tumour necrosis factor-α, and decorin in goat skin fibroblast cells - Wang Lingling; Lu Bingzhou; Zheng Haixue; Zhang Keshan; Liu Xiangtao (Journal of Veterinary Research, 2016)
Introduction: Orf virus (ORFV) is a prototype Parapoxvirus species in the Poxviridae family that causes serious zoonotic infectious disease. Goat skin fibroblast (GSF) cells are the major host targets of ORFV. Interleukin 8 (IL-8) and tumour necrosis factor (TNF)-α are known to play a vital role in immune response during viral infections. However, the manner of variation over time of their level of expression in GSF cells remains unclear.